2011
DOI: 10.1111/j.1365-263x.2011.01174.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a calcium hydroxide/chlorhexidine paste as intracanal dressing in human primary teeth with necrotic pulp against Porphyromonas gingivalis and Enterococcus faecalis

Abstract: The association of chlorhexidine with calcium hydroxide did not increase the antibacterial activity of the intracanal medication in the treatment of primary teeth with necrotic pulp with and without furcal/periapical lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 26 publications
(82 reference statements)
0
34
1
3
Order By: Relevance
“…This study revealed that calcium hydroxide, pure or associated with chlorhexidine and 20% glycolic ginger extract, was effective on the micro-organisms tested. The antimicrobial action of Ca(OH) 2 has been demonstrated in other studies [9,21]. Even though reports demonstrate that Ca(OH) 2 is not effective on Enterococcus faecalis [22], it presented 100% effectiveness in this study.…”
Section: Discussioncontrasting
confidence: 69%
“…This study revealed that calcium hydroxide, pure or associated with chlorhexidine and 20% glycolic ginger extract, was effective on the micro-organisms tested. The antimicrobial action of Ca(OH) 2 has been demonstrated in other studies [9,21]. Even though reports demonstrate that Ca(OH) 2 is not effective on Enterococcus faecalis [22], it presented 100% effectiveness in this study.…”
Section: Discussioncontrasting
confidence: 69%
“…The fnal results of the search in Medline (via PubMed), EMbase, EBSCOhost, The Cochrane Library, SciELO, and BBO were 77, 65, 17, 3, 4, and 7 studies, respectively. After the primary review, 44 studies 2-8,14-16,20,22,26-30,35,40,50,52,55-57,62-64,67,68,71,72,80,85,89,95,97,98,102,104,105,107,113-115 were considered relevant, and 40 studies 1,9,10,13,19,24,25,31,34,38,42-44,46-49,51,53,54,58-60,65,66,69,75-79,81,83,86,94,103,106,110-112 were irrelevant. Inter-observer agreement (Cohen kappa) was 0.93.…”
Section: Resultsmentioning
confidence: 99%
“…Studies on the efficacy of lasers in endodontic therapy have mostly focused on permanent teeth [10], while studies on primary teeth have been rarely reported. Meanwhile, because of the complicated anatomical structure of the pulpal chamber [11], choosing the most effective disinfection protocol for pulp-infected primary teeth becomes particularly important.…”
Section: Introductionmentioning
confidence: 99%